ISLAMISASI ILMU PENGETAHUAN PERSPEKTIF M. NAQUIB AL-ATTAS - Sutrisno, Andri (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
In the western modern century it was the main mecca of science for all countries of the world. With the first conference of International Islamic education in Makah in 1977 AD. In the conference, he offered the concept of islamization of science which is a response to the doctrine of the spread of science from the west. This approach uses descriptive qualitative with the type of literature research to find and analyze M. Naquib Al-Attas's thinking about the islamization of Science logically and systematically. While the focus of this research can be divided into two parts: 1. What is the biography of the life of M. Naquib Al-Attas? what is the concept of islamization of science perspective M. Naquib Al-Attas ?. The result of this study is M. Naquib Al-Attas is a descendant of the Prophet Muhammad SAW. And an academic who many of his notebooks. And the Islamization of science that it offers is that all science comes from Allah SWT. which is then interpreted by man.